Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea) - Hara, Marcos R.; Bragagnolo, Cibele; Pinto-Da-Rocha, Ricardo (Zootaxa, 2017)
Gonyleptid systematics has changed considerably in recent years, thanks to the increasing number of opilionologists and use of new data sources to infer relationships. This scenario promotes revisions of yet unrevised or recently proposed supraspecific groups. In an ongoing revision of the Gonyleptidae subfamilies Pachylinae, Ampycinae and some species of Cranainae (former Cranaidae), we found that Thaumatocranaus Roewer, 1932, a hitherto monotypic cranaine genus, is currently misplaced. According to the recent characterization of gonyleptid subfamilies and its close families, it should be transferred to Ampycinae based on pedipalpal and penial characters. This genus is revised, including redescription of its type species, T. mirabilis Roewer, 1932, and description of two new species, both from Colombia, Amazonas: T. magnificus sp. nov. (from Araracuara) and T. splendidus sp. nov. (from Leticia). The relationship of this genus with other Ampycinae genera is also discussed.